High rate of human enteroviruses among clinically suspected meningitis cases at selected Hospitals in Addis Ababa, Ethiopia - Ashenafi Alemu Wami (Public Library of Science (PLoS), 2021)
Background Because of limited infrastructure and skilled human capital, the etiology of meningitis is rarely identified in developing countries like Ethiopia. This results in unnecessary antibiotics use, economic crisis, hospitalization, and related nosocomial infections. Thus, we aimed to assess the epidemiology of human enteroviruses (HEVs) among clinically suspected meningitis cases in Addis Ababa, Ethiopia. Method A cross-sectional study was conducted from January to August 2020 at selected Hospitals in Addis Ababa, Ethiopia. Reverse transcriptase-polymerase chain reaction (RT-PCR) was conducted on cerebrospinal fluid (CSF) collected from 146 clinically suspected meningitis and bacterial culture-negative patients. SPSS v 21.0 was used for data analysis and bivariate correlation was done for the association between variables of interest. Results HEVs were detected in 39 (26.7%) of the 146 clinically suspected meningitis cases. Most of the HEVs cases 28 (71.9%) were detected in younger-aged infants less than 1 year. The most commonly observed clinical manifestations were vomiting (75.5%) followed by fever (56.8%) and impaired consciousness or irritability (50.7%). The mean length of hospital stay for patients with enteroviral meningitis was 9 days. Many patients with HEVs were recovered with sequelae (46.2%), and HEVs has contributed for one out of the nine meningeal deaths (11.1%). Conclusions HEVs were found to be the commonest cause of morbidity and mortality in all age groups. Many of the patients were mistreated with antibiotics and hospitalized. The detection of HEVs in 26.7% of clinically suspected meningitis cases indicated the need for molecular tests in investigating the etiology of meningitis. Therefore, we suggest the introduction of molecular tests as a routine practice in referral hospitals and the need to further characterize circulating HEVs strains.